Creating Interactive Learning Environments through the Use of Information and Communication Technologies Applied to Learning of Social Values: An Approach from Neuro-Education - Luis Espino-Díaz; Jose-Luis Alvarez-Castillo; Hugo Gonzalez-Gonzalez; Carmen-Maria Hernandez-Lloret; Gemma Fernandez-Caminero (Social Sciences, 2020)
In order to link learning and the brain, it is necessary to carry out a restructuring of pedagogical practice so that it can be linked to the contributions of Neurosciences. In this sense, Neuro-education is emerging as a new science that has as its main objective the synergy of Pedagogy, Cognitive Psychology and Neuroscience, and with this, being able to bring the different educational agents the necessary resources in terms of the brain and learning binomial This article focuses on the importance of education in values, and the acquisition of prosocial behavior and how this educational field can be developed from the use of information and communication technologies (ICT). The challenge before us is to build the map of values, which make the individual a fulfilled being and, in turn, a collaborator of the social environment. On the other hand, ICTs offer enormous potential in terms of their application in the field of education. In this article we will show the role that this type of tools can play in the learning and assimilation of values, bearing in mind the contributions of neuro-education.